Análise dos aspectos da relação social entre crianças : contribuições para a inclusão na educação infantil - Rodrigues, Renata Suzi Escudeiro Hastenreiter (2011)
The current study presents the research developed in the Master’s degree course of Education, in the line of research “Diversity and inclusive educational practices”, part of the Post-Graduation Program at the Espírito Santo Federal University, titled “Analysis of aspects of the social relation among children: contributions for the inclusion in the children’s education”. The paper aims at reaching the objectives of knowing the main aspects of the social relations established between a disabled child and the others in a regular children’s education school and identify the implications of such relations to the childhood of the disabled child and to the processes of inclusion in the school environment. To do so, the work made an ethnographic study-case, which uses to collect data: the participant observation with field diary registry, the semi structured interview, the micro ethnographic and documental analysis. Two disabled children who study in an Education Municipal Center (CMEI), in the district of Serra, State of Espírito Santo participated of the research. Referentially, it uses the assumptions of the Historical-Cultural Theory, from L.S. Vigotski, in order to understand the concepts of social relation, subjectivity, cultural constitution, mediation, deficiency, childhood and education of disabled children, and M. Bakhtin contributions on the phenomenon of the dialogic relation between children, polyphony, polysemy, to the Other one position in the development of I-Child and the I-Researcher of the Childhood. To analyze data, it uses six categories that identify the main aspect unveiled in the social relations among children: the language as representative function; the acts of command/obedience as movements which members of a social group are reciprocally affected; the dynamic tension/balance in the construction of the individuality; the imitation as one of the forms of social representation; the affectivity in the relation myself  others; and the games as aspect of the relation among children. As result, the study unveils the complex net of social relations that constitute the school experience and their implications to the development, to the constitution of the childhood and the school inclusion of disabled children.